Informative Treatment of violence against women in Ecuador - Córdova Torres, Ana Isabel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The media are a powerful tool for transmitting information. They have the ability to influence, re-educate, sensitize or desensitize a population depending on the treatment they give to their publications. However, the frequent use of shocking phrases, discriminatory titles present women as the person who provokes the aggression, reinforcing the violence against them. In this sense, this article analyzes the headlines presented in the Extra newspaper publications during the year 2021, about five cases of femicide, with the intention of determining to what extent there is social responsibility on the part of the media.